IMPLEMENTASI PENDIDIKAN SENI DALAM MEMPERTAHANKAN KARAKTERISTIK BANGSA PADA GENERASI MILENIAL - Anik Purwati (Institut Islam Mamba'ul 'Ulum Surakarta, 2019)
Social media is a vehicle that can be used to develop students' digital and modern creativity. The use of social media is certainly in line with the development of each generation with the characteristics of each generation. Millennials are a generation with significant technological change, must be able to face challenges, develop and be able to utilize technology without having to change its characteristics. There are four steps that must be taken to maintain the characteristics of the nation through art education: (1) having knowledge related to the learning climate in the classroom, (2) abilities related to learning management strategies, (3) having abilities related to providing feedback and strengthening, and (4) having abilities related to self-improvement.